Agro-Morphological Characterization and Estimation of Genetic Parameters of Spring Maize Hybrids in the Inner Plains of Far-West Nepal - Prachi Bista; Sandesh Thapa; Sara Rawal; Deependra Dhakal; Darbin Joshi (International Journal of Agronomy)
Heat resilient maize hybrids are an important input in maize cultivated area coupled with high temperature during the flowering period, with a specific focus on the Terai region of Nepal. The research was conducted in the Dhangadhi district from April 2020 to August 2020 in an alpha-lattice design with 26 genotypes and two replications. Analysis of variance suggests that genotypes were significantly different for all traits except plant height and plant population. The phenotypic coefficient of variation (PCV) was higher than the genotypic coefficient of variation (GCV) for all traits. High PCV and GCV values were found in the anthesis silking interval, ear aspect and grain yield and low values in the anthesis days and silking days. Highly heritable traits were days to 50% tasseling (0.74), days to 50% silking (0.74), ear aspect (0.69), number of rows per cob (0.84), number of grains per row (0.61), cob diameter (0.87), and cob length (0.86). Genetic advance ranged from the lowest in plant height to the highest in anthesis silking interval. Correlation studies revealed that grain yield showed a negative and significant correlation with reproductive traits, while a positive and significant correlation between ear height and number of ears per hectare was observed. Cluster analysis grouped 26 genotypes into 5 major clusters, and the intracluster distance ranged from 4034.3 to 34960.3. Thus, traits having high variation can be used as selection indices for indirect selection for the improvement of maize productivity and suggest genotype like ZH182079, ZH1767, and KH15486 with high yield for commercialization and distribution to farmers.